2011
DOI: 10.2134/agronj2010.0288
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Requirements for Ethanol Production from Sweet and Photoperiod Sensitive Sorghums in the Southern High Plains

Abstract: Sorghum (Sorghum bicolor L. Moench) has high water use efficiency, and is therefore widely cultivated in the Southern High Plains (SHP). Interest in sorghums for biofuel feedstock has increased recently as ethanol demand expands. Unlike grain sorghum, little data are available on N fertilizer requirements for ethanol production from sweet or forage sorghum production. Our objective was to compare ethanol yields and determine optimal N fertilizer needs for ethanol production from sweet sorghum and photoperiod s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
49
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 21 publications
12
49
0
4
Order By: Relevance
“…Based on this analysis, an optimum N application rate of 90 kg ha -1 is recommended. Similar results were also reported by Erickson et al (2012) and Tamang et al (2011). Nitrogen use efficiency values were estimated relative to yield observed in controlled plot, so that NUE values in Figure 2 represent increment in gross income per unit addition of N fertilizer.…”
Section: Nitrogen Responsesupporting
confidence: 78%
See 1 more Smart Citation
“…Based on this analysis, an optimum N application rate of 90 kg ha -1 is recommended. Similar results were also reported by Erickson et al (2012) and Tamang et al (2011). Nitrogen use efficiency values were estimated relative to yield observed in controlled plot, so that NUE values in Figure 2 represent increment in gross income per unit addition of N fertilizer.…”
Section: Nitrogen Responsesupporting
confidence: 78%
“…Similar trends for N response of sweet sorghum were reported by Wiedenfeld (1984) and Tamang et al (2011). Marginal product (MP) curves for biomass yield and ethanol yield are presented in Figure 1A and Figure 1B, respectively.…”
Section: Nitrogen Responsesupporting
confidence: 77%
“…These genetic advancements would be significant in water limited regions, particularly in areas where there is livestock demand for highly digestible forages, and first generation ethanol plants accept sorghum grain. Tamang et al [34] reported an optimum N rate of 108 kg ha −1 for two photoperiod sensitive and two sweet cultivars in the Texas Southern High Plains. Haankuku et al [35] reported an optimal N rate of 100 kg ha −1 in Oklahoma with no supplemental irrigation, but there was no yield response during drought.…”
Section: Annual Cropsmentioning
confidence: 99%
“…Conservation tillage increased biomass by 11 % during the dry year, but no difference was observed between tillage systems for the wet year [36]. In the Southeast, sweet and photoperiod sensitive sorghums have been examined as potential energy crops due to high biomass production, low N requirements, and drought tolerance relative to corn [34,[36][37][38]. Sweet sorghum has additional benefits of a typically shorter growing season and production of fermentable sugars, although biomass production is reduced compared to photoperiod sensitive sorghum [34,38].…”
Section: Annual Cropsmentioning
confidence: 99%
See 1 more Smart Citation